Pengaruh Pertumbuhan Ekonomi, Indeks Pembangunan Manusia (IPM), Tingkat Pengangguran Terbuka Terhadap Tingkat Kemiskinan di Provinsi Kalimantan Selatan - Hayati, Norlaila; Chandriyanti, Ika (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2025)
The research was conducted to test and analyze theinfluence of economic growth, the human development index and the open unemployment rate on poverty levels in South Kalimantan Province. This research method is literature data obtained from the Central Statistics Agency of South Kalimantan Province. The analysis tool uses the multiple regression analysis method assisted by the Eviews 10. The research results show that simultaneously Economic Growth, Human Development Index, and Open Unemployment Rate influence the Poverty Rates in South Kalimantan Province. Partially, Economic Growth has no effect on the Poverty Rates in South Kalimantan Province, while the Human Development Index and Open Unemployment Rate have an effect on the Poverty Level in South Kalimantan Province. Of these three variables, the most dominant variable is the Human Development Index which influences the level of poverty in South Kalimantan Province.